Profile of Caesarean Section in Kirtipur Hospital - Pradhan, P; Shrestha, S; Rajbhandari, P K; Dangal, G (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to find out the incidence and outcome of caesarean sections done at Kirtipur Hospital. Methods: This was a retrospective study conducted from 1st January 2009 to 31st December 2013. Case files of 660 patients who underwent caesarean section for various indications were analyzed for incidence, indication of caesarean section, booking status, parity, and maternal and fetal outcomes. Results: Out of 1295 deliveries, 50.9% (n=660) had caesarean section. Most of the caesarean section was done for fetal distress (40.2%; n=265) and on account of previous history of caesarean section (13.5%; n=89). Majority of caesarean section (44.4%, n=293) was done in age group of 25-29 years. Among them, 65.9% (n=435) were nulliparous. There were 35.3% (n=563) booked cases. Emergency caesarean sections were performed in 62.4% (n=412) cases. Maternal morbidity was less (7.2%, n=48). Conclusions: The study showed high rate of caesarean section. The most common indication was fetal distress. Post-operative complications and fetal outcome were within acceptable range. DOI: http://dx.doi.org/10.3126/njog.v9i2.11763